Temporal and spatial variability of surface mass balance at Dome Fuji, East Antarctica, by the stake method from 1995 to 2006 - KAMEDA, Takao; MOTOYAMA, Hideaki; FUJITA, Shuji; TAKAHASHI, Shuhei (International Glaciological Society, 2008)
The surface mass balance (SMB) at Dome Fuji, East Antarctica, was estimated using 36 bamboo stakes (grid of 6 × 6, placed at 20 m intervals) from 1995 to 2006. The heights of the stake tops from the snow surface were measured at 0.5 cm resolution twice monthly in 1995, 1996, 1997 and 2003, and once a year for the rest of the study period. To account for snow settling, the average snow density at the stake base during the measurements was used for converting the stake-height data to SMB. The annual SMB from 1995 to 2006 at Dome Fuji was 27.3 ± 1.5 kg m−2 a−1. This result agrees well with the annual SMB from AD 1260 to 1993 (26.4 kg m−2 a−1) estimated from volcanic signals in the Dome Fuji ice core. Over the period 1995–2006, there were 37 (8.6% of the measurements) negative or zero annual SMB results. Variation in the multi-year averages of annual SMB decreased with the square root of the number of observation years, and 10 years of observations of a single stake allowed the estimation of annual SMB at ±10% accuracy. The frequency distributions of annual and monthly SMB were examined. The findings clarify the complex behavior of the annual and monthly SMB at Dome Fuji, which will be common phenomena in areas of low snow accumulation of the interior of the Antarctic ice sheet. journal article